Концепция консолидации информации как элемент бизнес-этики обеспечения экономической безопасности организации - Юрьева, Ирина Анатольевна (My University, 2017)
В статье рассмотрены проблема внедрения элементов бизнес-этики в концепции консолидации информации для обеспечения экономической безопасности организации, а также необходимость применения принципов консолидации информации в организации и внедрение системы управления знаниями. Определена необходимость внедрения элементов бизнес-этики для максимизации конкурентных преимуществ организации в контексте обеспечения системы экономической безопасности организации.

In the article the problem of implementing business ethics elements in a concept of information consolidation with a purpose to provide economic security of an organization has been considered, as well as a necessity to apply principles of information consolidation in an organization and implement a system of knowledge management. A necessity of implementing business ethics elements to maximize competitive advantages of an organization in context of providing an organization with a system of economic security.
The concept of information consolidation as an element of business ethics in providing economic security of an organization
Keywords: консолидированная информация; принятие решений; внутренняя угроза; внешняя угроза; управление; consolidated information; decision taking; internal threat; external threat; management